(untitled) (Journal of the College of Basic Education, 2023)
research aims to: build an educational program based on analytical thinking and knowing the effectiveness of the educational program in developing the grammatical skills of the fifth grade literary students, and to achieve the first goal of the research: the researcher followed the procedures of the descriptive approach to build the educational program, and to achieve the second research goal: the researcher adopted the experimental approach And the design of the control group with a post-test was used, and the researcher put the following zero hypothesis: There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group and the control group. The researcher randomly chose his research sample consisting of (68) students From Dirar Ibn Al-Azwar Preparatory School, with (34) students from Division (A) and (34) students from Division (B), and the researcher prepared a test to measure the development of grammatical skills. It began on Wednesday corresponding to 10/12/2022 and ended on Tuesday corresponding to 1/31/2023. The researcher recommended to benefit from the educational program in teaching Arabic grammar in the preparatory stage